Bacterial Desulphurization of Coal from Jaworzno Mine - Peter Fecko; Pavla Ovcarí; Barbara Tora; Hong Nguen Vu (International Mineral Processing Congress, 2003)
The aim of this paper is to evaluate the suitability of a coal sample from the mine Jaworzno (Poland)- locality for bacterial leaching. Laboratory research used a pure bacterial culture of Thiobacillus ferrooxidans. The results showed that bacterial leaching was effective, with a one month leaching time, when 65% of total sulphur and 85% of pyritic sulphur was leached. The paper describes changes to the pyrite during and after bacterial leaching.